Penatalaksanaan Laki-Laki Usia 20 Tahun Dengan Skabies Melalui Pendekatan Kedokteran Keluarga di Wilayah Kerja Puskesmas Tanjung Sari Natar - Khairunnisa, Salma; Angraini, Dian Isti (CV. Jasa Sukses Abadi, 2025)
Scabies is a skin disease caused by infestation and sensitization with the parasite Sarcoptes scabiei var. hominis. Other names or synonyms of scabies are